Complete Heart Block in Hypertrophic Cardiomyopathy: A Rare Association - Dubey, L.; Guruprasad, S.; Battacharya, R.; Subramanyam, G. (Kathmandu University Medical Journal, 2017)
Ventricular tachyarrhythmias are common in hypertrophic cardiomyopathy that may lead to syncope and sudden death. Bradyarrhythmia such as atrioventricular conduction disturbance, a relatively rare complication associated with hypertrophic cardiomyopathy, may also cause syncope and sudden death in hypertrophic cardiomyopathy. We report a 28-year old man who was diagnosed as a case of hypertrophic cardiomyopathy presented with syncope and complete heart block. Subsequently, a permanent pacemaker was implanted to the patient.